Effects of Co nanoparticle addition to Sn-3.8Ag-0.7Cu solder on interfacial structure after reflow and ageing - Haseeb, A.S. Md. Abdul; Leng, T.S. (2011)
Effects of Co nanoparticle additions to Sn-3.8Ag-0.7Cu on the structure of solder/copper interface have been studied after reflow and high temperature ageing (150 degrees C, up to 1008 h). Results show that the Co nanoparticles substantially suppress the growth of Cu(3)Sn but enhance Cu(6)Sn(5) growth. Cobalt nanoparticles reduce interdiffusion coefficient in Cu(3)Sn. It is suggested that the Co nanoparticles undergo surface dissolution during reflow and exert their influence, at least partially, through alloying effect. (C) 2011 Elsevier Ltd. All rights reserved.